Intergenerational differences in memories of Yugoslavia – the case of Slovenia - Vintar Mally, Katja; Resnik Planinc, Tatjana (Geographica Pannonica, 2019)
Over the 50-year history of Yugoslavia, there were rises and falls, successes and failures, bright and dark moments. It is thus not surprising that the many memories that people have of life in Yugoslavia are often diametrically opposed. These divergent memories of Yugoslavia are the central topic of our research. The study focuses on memories and their transmission from older to younger generations and is based on the results of a survey that was carried out in the Republic of Slovenia. The research has clearly shown that positively tinged memories of Yugoslavia predominate in the families of younger as well as older generations on the one hand while on the other hand it has become obvious that Yugonostalgia is nostalgia for something from the past and it is not a desire to experience or revive that in the present.